Essays on Regional Economics - Kopsch, Fredrik (KTH, Bygg- och fastighetsekonomi, 2013)
This thesis is, to its nature, somewhat wide in scope. The common denominator for theincluded essays is regional economics. Within this very wide area of research, the thesis isdivided rather sharply between one part regarding trading of emission permits in theinternational aviation sector and another part concerned with real estate markets. The basis ofthis thesis is five essays all written for the purpose of peer reviewed publication.The first topic includes three essays; the first provides an overview of previous emissionstrading schemes which allow us to learn for future policy designs when including new sectorsor creating new trading schemes. The second essay aims at estimating elasticities for domesticair travel in Sweden. The third essay, takes an analytical approach to scrutinizing theproposed barrier of trade between the international aviation sector and the stationary sourceswithin the EU ETS.The second topic is motivated by the structural relocations that two municipalities in thenorthern part of Sweden are currently undergoing. The first essay on this topic, the fourthessay of this thesis, concerns redistributions of wealth that occur when moving a city center.The fifth and final essay approaches the problem of measuring an effect of information onhouse values with small quantities of data, such as is the case for Gällivare municipality. QC 20131024